2012
DOI: 10.1074/jbc.m111.315309
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Viral Ortholog of Human DNA Glycosylase NEIL1 Bound to Thymine Glycol or 5-Hydroxyuracil-containing DNA

Abstract: Background: Nei is a DNA glycosylase of the base excision repair pathway. Results: We present two crystal structures of an Nei bound to thymine glycol or 5-hydroxyuracil. Conclusion: Mutational analysis of active site residues suggests that lesion recognition happens before the damaged base is everted into the active site. Significance: These are the first structures of any Nei in complex with a damaged base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 61 publications
4
79
0
Order By: Relevance
“…For oxoG-recognizing Fpg proteins, the similar lesion recognition loop is much longer, although the lesion recognition loops of Bacillus stearothermophilus Fpg (BstFpg) and Lactococcus lactis Fpg were either visible or disordered in different structures (36,38,39); for Arabidopsis thaliana Fpg which does not excise oxoG, its corresponding loop was found to be in one uniform conformation in the apo and THF-bound structures (40). For the Tg-recognizing MvNei1, only one conformation was observed for the corresponding loop in the apo, THF-and Tg-bound structures of MvNei1, which mostly resembles the THF-bound NEIL1 structure (33,34). Nevertheless, our structures revealed that the lesion recognition loop of NEIL1 can adopt multiple conformations, and this flexibility is important for optimal substrate binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For oxoG-recognizing Fpg proteins, the similar lesion recognition loop is much longer, although the lesion recognition loops of Bacillus stearothermophilus Fpg (BstFpg) and Lactococcus lactis Fpg were either visible or disordered in different structures (36,38,39); for Arabidopsis thaliana Fpg which does not excise oxoG, its corresponding loop was found to be in one uniform conformation in the apo and THF-bound structures (40). For the Tg-recognizing MvNei1, only one conformation was observed for the corresponding loop in the apo, THF-and Tg-bound structures of MvNei1, which mostly resembles the THF-bound NEIL1 structure (33,34). Nevertheless, our structures revealed that the lesion recognition loop of NEIL1 can adopt multiple conformations, and this flexibility is important for optimal substrate binding.…”
Section: Discussionmentioning
confidence: 99%
“…Although the crystal structure of NEIL1 protein is determined (32), a complex structure of NEIL1 bound to duplex DNA has not been reported. Recent studies have determined several complex structures of MvNei1 (mimivirus Nei1), a viral ortholog of human NEIL1 (33,34). However, MvNei1 and NEIL1 have apparent differences in their 3D structures and enzymatic properties (5).…”
mentioning
confidence: 99%
“…However, FapyG is recognized even when this loop is deleted (42). There are currently no structures of bacterial Nei or Nth with lesions in the substrate binding pocket, but the structure of a viral ortholog of human NEIL1, MvNei, has been solved with Tg or 5-hydroxyuracil in the binding site pocket (43). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As yet there are no structures of the mammalian glycosylases that recognize oxidized pyrimidines (NTH1 and the three NEIL proteins) with DNA lesions in the substrate binding pocket. However, the structures of two viral orthologs of the NEIL proteins, mimivirus Nei1 and Nei2, have been solved in complex with DNA, and in the case of mimivirus Nei1, with lesions in the active site [23,24]. The latter structures together with site-specific mutagenesis clearly show that there are no specific interactions between amino acid residues in the glycosylase and the lesion, supporting prior hypotheses that the lesion search must occur before extrusion of the DNA base.…”
Section: Base Excision Repair Enzyme Structures Inform Functionmentioning
confidence: 99%